Elaboración de un programa en autocad 3d para realizar análisis anticolisión de pozos petroleros del bloque tarapoa - Gencón Torres, Jose Carlos (2010)
This project grew out of an exhibition in the company Andespetroleum on Collision Analysis of oil wells using "COMPASS" Halliburton Landmark program. The analysis was delivered to the customer by means of a numerical report, which should be interpreted by the individual in the directional control wells. Thinking that this analysis could be performed by visualizing the wells collision of a pad in three dimensions, in the course of the months was sought to reach a practical program, friendly and efficient for the intended purpose. In Chapter 1, we see an introduction to the compilation of this thesis, we will know why it is important to address this issue, which seeks to project objectives and what are the assumptions with which we started to reach our meta.En Chapter 2, will address the issue location, geology, lithology, history and development of Block Tarapoa. In chapter 3, we can appreciate the history of the first instruments to measure the slope of the wells drilled down to the modern equipment used to transport telemetry information depth, inclination and azimuth.En Chapter 4, we see a theoretical information on Visual Basic Aplication in order to get into the world of objetos.Y finally oriented programming power in Chapter 5, find if it succeeded or not make a tool so we can make a collision avoidance analysis graphically in 3 D.